Power of Like-Minded Companionship: Role of Social Benefits in Breeding Blogging Intention - Ho, Ying; Mac, Lancy Vai Iun; Lin , Yinxi (International Journal of Management and Business, 2024)
Web bloggers are generally regarded as more credible than commercial sources, making them an ideal source for brand endorsement. Yet very few blogging research look specifically at the interaction process of the blogger-reader duo. This study highlights social interaction between blogger-audience duo as a crucial element in blogging activities. It investigates the influence of blogger reader homophily on blogging continuance intention, and explains this relationsmhip by the relational benefits and positive support bloggers obtain via blogger-reader interactions. Data were collected from 200 Chinese bloggers who have shared product/service comments in popular Chinese online social networks. Results suggest that social rewards (i.e., relational benefits and positive support) generated by interpersonal interactions in the blog community encourage bloggers to continue blogging. Our findings underscore the significant roles of blogger-audience homophily and emotional rewards bloggers gained from blogging interactions in enhancing blogging intention. Managerial implications on how company managers and social network operators can effectively manage their online platform are also discussed.